Models of Religious education: the experience of Europe - Мустaфaевa A. A. (Journal of Oriental Studies, 2017)
This article attempts to examine the experience of some European countries in the classification of religious instruction models. Religious instruction, depending on the socio-cultural, political and religious values and factors is performed on special models. It is known that religious instruction, depending on its place in society and a country goes through a certain dynamic. So, in the first countries where the functioning state church, religious education is compulsory in the second country, where it is separated the state from religion (church and state) religious instruction – forbidden, and in the last – third, where between state and religion established relationships, religious training is carried out on the basis of a number of agreements – harmony. Choosing the right model of religious education reveals a number of constants.